If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 8y = -7 + 3 Combine like terms: -4y + 8y = 4y 4y = -7 + 3 Combine like terms: -7 + 3 = -4 4y = -4 Solving 4y = -4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '4'. y = -1 Simplifying y = -1
| 11x-19=5x+5 | | 4x+36=6x+14 | | 8x+6=5x+21 | | 9x-25=47 | | 8y+6=-4+2y | | -5w-9w=15+7 | | 7x+3=38 | | -2x-6x=11-17 | | 1x-16=-10 | | 7y+3y=-20-13 | | -8+11=-5v+2v | | 5y-4=6y | | 4z+6=5z+4 | | 3z-7=4z | | 3(10)+15= | | 5z-8=4z-2 | | 1x-17=-12 | | 3x+26=17+3x | | 3x-10=6x+4 | | 92-3x=24x+23 | | 111-3x=5x+23 | | 4(x-2)=16 | | -32-3x=13-8x | | 3x-9=-3 | | 4x+5=-73-9x | | 1x+25=20 | | 92-6x=9x+17 | | 7x+5=61 | | 6x+9=51 | | 5y=40 | | 16x-4x+6=12x-2+8 | | 7x+10=94 |